The Generalized Internal/External Frame of Reference Model: An Extension to Dimensional Comparison Theory - Möller, Jens (Frontline Learning Research, 2016)
The dimensional comparison theory (DCT) is based on the internal/external frame of reference model (I/E model). The model focuses on the effects of external (e.g., “How good am I in math compared to my classmates?”) and internal, dimensional comparisons (e.g., “How good am I in math compared to English?”) on academic self-concepts with widespread consequences for students’ self-evaluation, motivation, and behavioral choices. This article presents an extension to the DCT: The proposal of a generalized internal/external frame of reference model (GI/E model that allows the application of previous findings on academic self-concepts to a variety of domain-specific comparison targets and standards. On the side of targets and standards it not only deals with the academic area but also with other areas, which are compared intra-individually. On the side of the consequences, it deals with other variables besides self-concepts, i.e. with motivational constructs, (learning) behaviors or personality characteristics as the outcomes of external and dimensional comparison processes. The present article closes with an examination and discussion of the contributions of the DCT by applying standards of good theories to it.